Design and implementation of autonomous mobile device with adaptive control - Juhasova, Bohuslava; Halenar, Igor; Juhas, Martin (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
The problem of autonomous vehicles mobility and their orientation in space is an important issue today in the manufacturing sector, especially in relation with the application of standard Industry 4.0. In our paper is presented the design of autonomous mobile device. When designing device, we focused on its wide usability and flexibility in deployment, which was reflected in its architecture. The proposal of device contents necessary sensor system, an important part of the device is system for image processing in real time with sufficient computing capacity. Device computing capacity allows to use more complex control algorithms for orientation in space. Final design include communication channels redundancy for the case of failure of any part of the system. For the implementation of control algorithms was chosen software tool Matlab and its toolbox Simulink.